2012
DOI: 10.1371/journal.pone.0051684
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Screen for Olfactory Habituation Mutations in Drosophila: Analysis of Novel Foraging Alleles and an Underlying Neural Circuit

Abstract: Habituation is a form of non-associative learning that enables animals to reduce their reaction to repeated harmless stimuli. When exposed to ethanol vapor, Drosophila show an olfactory-mediated startle response characterized by a transient increase in locomotor activity. Upon repeated exposures, this olfactory startle attenuates with the characteristics of habituation. Here we describe the results of a genetic screen to identify olfactory startle habituation (OSH) mutants. One mutation is a transcript specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 66 publications
(93 reference statements)
0
35
0
Order By: Relevance
“…With the exception of an unbiased, forward genetic screen for olfactory habituation mutants in Drosophila (Eddison et al, 2012; Wolf et al, 2007), only candidate gene approaches have been used to identify and dissect genetic mechanisms underlying habituation (Castro-Alamancos and Torres-Aleman, 1994; Das et al, 2011; Engel and Wu, 1998; Lau et al, 2012; Morrison and van der Kooy, 2001; Ohta et al, 2014; Rankin and Wicks, 2000; Rose et al, 2003; Sanyal et al, 2004; Swierczek et al, 2011; Typlt et al, 2013). To complement previous work and identify a broad set of core genes critical for vertebrate startle habituation, we conducted a classical three generation forward genetic screen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the exception of an unbiased, forward genetic screen for olfactory habituation mutants in Drosophila (Eddison et al, 2012; Wolf et al, 2007), only candidate gene approaches have been used to identify and dissect genetic mechanisms underlying habituation (Castro-Alamancos and Torres-Aleman, 1994; Das et al, 2011; Engel and Wu, 1998; Lau et al, 2012; Morrison and van der Kooy, 2001; Ohta et al, 2014; Rankin and Wicks, 2000; Rose et al, 2003; Sanyal et al, 2004; Swierczek et al, 2011; Typlt et al, 2013). To complement previous work and identify a broad set of core genes critical for vertebrate startle habituation, we conducted a classical three generation forward genetic screen.…”
Section: Discussionmentioning
confidence: 99%
“…Inspired by behavioral screens in Drosophila and C. elegans (Benzer, 1967; Brenner, 1974; Eddison et al, 2012; Ikeda et al, 2008; L'Etoile et al, 2002; Lau et al, 2012; Pierce-Shimomura et al, 2008; Rankin, 2004; Rankin et al, 1990; Swierczek et al, 2011; Wolf et al, 2007), we performed a forward genetic screen using a high throughput behavior testing apparatus that measures zebrafish startle habituation (Wolman et al, 2011), and then applied whole genome sequence (WGS) analysis to molecularly identify the mutated genes. Here, we report on: i ) a set of 14 mutants with specific deficits in startle habituation, ii ) the molecular identification of two mutants, and iii ) the characterization of a novel and vertebrate specific modulator of zebrafish habituation learning.…”
Section: Introductionmentioning
confidence: 99%
“…Recognizing the important role of the second messenger cGMP in NO signaling, we tested for the involvement of the cGMP-dependent kinase Foraging, dg2, or PKG in axon regeneration. The foraging ( for ) locus produces 11 transcripts encoding four protein isoforms (Davies, 2006), among which nine encode the three major FOR protein isoforms FOR-T1, T2, and T3 (Figure S7A) (Eddison et al, 2012). We found that class III da neuron axon regeneration was significantly boosted in a mutant allele of for for k047037 (Figures 7A–7D), an allele with a P-element inserted in the intron, disrupting mRNA splicing and reducing transcript expression of the for-T1 and T3 isoforms (Figures S7A and S7B).…”
Section: Resultsmentioning
confidence: 99%
“…19–12-Gal4 (Xiang et al, 2010), reop-Gal80 (Awasaki et al, 2008), DmPiezoKO , UAS-DmPiezoRNAiv2796 , DmPiezo-Gal4 (Kim et al, 2012), ppk-CD4-tdGFP (Han et al, 2011), ppk-Gal4 (Han et al, 2011), NompC-QF (Petersen and Stowers, 2011), QUAS-mCD8GFP (Potter et al, 2010), QUAS-mtdTomato (Potter et al, 2010), UAS-CD4TdTomato (Han et al, 2011), UAS-CamKII-I.Ala (Joiner and Griffith, 1997), UAS-CamKII RNAi (Ashraf et al, 2006), UAS-CamKII.T287D (Jin et al, 1998), Nos Δ15 (Yakubovich et al, 2010), Nos 1 , UAS-Nos (Lacin et al, 2014), for k04703 (Spradling et al, 1999), for 11.247 (Eddison et al, 2012), UAS-for-T1 (Belay et al, 2007), UAS-dg2-P1 , UAS-dg2-P2A (MacPherson et al, 2004), hsFLP;;UAS > CD2 > mCD8-GFP (Grueber et al, 2007), m12-Gal4 ( P(Gal4)tey 5053A ) (Ritzenthaler et al, 2000), GCaMP6s (Chen et al, 2013), Cam n339 (Heiman et al, 1996), NompC-LexA (Shearin et al, 2013) and tub-Gal80 ts (McGuire et al, 2003) have been previously described. UAS-Dcr-2 , for DfED243 , and UAS-forRNAiBL35158 were from Bloomington stock center.…”
Section: Methodsmentioning
confidence: 99%
“…; Eddison et al . ), but also rapidly switches to high thermal inducibility from a constitutively expressed isoform set (middle isoforms, RG:RB:RC ) and by invoking transcription of a rare isoform expressed usually expressed under few developmental/tissue stages (short isoform, RD ) (Graveley et al . ).…”
Section: Discussionmentioning
confidence: 99%